tacking and a tacktical methodology : moving towards a different politics for art - Bufardeci, Louisa (Early Modern History and Modern History E-Books Online, Collection 2024., 2025)
How can artists (and others) who find themselves in positions of privilege think differently about the way they do what they do in order to create the conditions for better, more just relations to flourish? Finding an answer to that question is at the heart of this book. After critiquing the relationship between contemporary art, race and privilege the author brings together First Nation and feminist philosophies of relationality, the game of string figuring, and her own history as an artist to propose an alternate methodology that puts relation at the centre of practice. She introduces the multivalent concept of "tacking"-a movement at an oblique angle to prevailing winds-in order to traverse the waters of contemporary art to challenge power and create a more just future. See Less